2014
DOI: 10.1007/s00128-014-1216-7
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Oil and Dispersed Oil on Juvenile Mud Crabs, Rhithropanopeus harrisii

Abstract: In order to simulate an offshore oil spill event, we assessed the acute toxicity of the non-dispersed and the chemically dispersed water-accommodated fraction (WAF) of crude oil using Louisiana sweet crude and Corexit(®) 9500A with juvenile Harris mud crabs (Rhithropanopeus harrisii), an important Gulf of Mexico benthic crustacean. The chemical dispersion of crude oil significantly increased acute toxicity of the WAF in juvenile mud crabs compared to naturally dispersed oil. The majority of the mortality in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…The increase in the toxicity of oil due to the addition of dispersant has been reported in many past studies (Fabregas et al 1984;Koyama and Kakuno 2004;Ramachandran et al 2004;Baek et al 2013;Lee et al 2013;Cohen et al 2014Anderson et al 2014). However, the results of this study showed that CEWAF of bunker C oil and DISP were both highly toxic.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The increase in the toxicity of oil due to the addition of dispersant has been reported in many past studies (Fabregas et al 1984;Koyama and Kakuno 2004;Ramachandran et al 2004;Baek et al 2013;Lee et al 2013;Cohen et al 2014Anderson et al 2014). However, the results of this study showed that CEWAF of bunker C oil and DISP were both highly toxic.…”
Section: Resultsmentioning
confidence: 97%
“…Added to this, exposure of periphyton to chemically dispersed oil led to reduced total abundance, with observations that algae exposed to higher concentrations could not become colonized (Baek et al 2013). The same increased toxicity was noted for zooplankton (Lee et al 2013;Cohen et al 2014), crustaceans (Anderson et al 2014) and fish (Koyama and Kakuno 2004;Ramachandran et al 2004) after exposure to chemically dispersed oil.…”
mentioning
confidence: 75%
“…Previous studies have looked at the effect of petroleum hydrocarbons on blue crabs (Wang and Stickle 1988). Since dispersants allow oil to mix more readily into the water column, chemically dispersed oil has been found to be significantly more toxic than non-chemically dispersed oil (George-Ares and Clark 2000; Ramachandran et al 2004;Khan and Payne 2005;Anderson et al 2014). We also focused on acute toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…The polycyclic aromatic hydrocarbon (PAH) fraction, consisting of aromatic benzene rings, forms a significant proportion of the wateraccommodated fraction (WAF) of both oil types. Previous studies show that PAHs can be toxic to marine organisms (Barron et al 2004;Couillard et al 2004;Incardona et al 2004Incardona et al , 2014Anderson et al 2009Anderson et al , 2014Scott et al 2011;Agamy 2012). Toxicity and the physiological mode of action differ between PAHs (Incardona et al 2004(Incardona et al , 2005(Incardona et al , 2006.…”
Section: Introductionmentioning
confidence: 96%
“…It is clear, however, from studies conducted elsewhere that oil contamination affects a range of marine taxa (Taban et al 2004;Aarab et al 2011;Almeda et al 2014aAlmeda et al , 2014bCohen et al 2014). In addition, the chemical dispersants often used to remove oil from surface waters may increase chemical toxicity in the surrounding media (Couillard et al 2004;Ramachandran et al 2004;Anderson et al 2009Anderson et al , 2014Schein et al 2009;Zhang et al 2013). It is important, therefore, that decision-makers have access to information regarding toxic thresholds of these contaminants and which species are most at risk.…”
Section: Introductionmentioning
confidence: 98%